THE ROLE OF THE GOVERNMENT IN WASTE MANAGEMENT IN TOMPO BALANG VILLAGE, MAKASSAR CITY - Pratiwi, Suci; Sakawati, Herlina; Nur, Andi Cudai; Purna, Zarni Adia (Universitas Negeri Makassar, 2025)
This research aims to determine the role of the government in waste management in Tompo Balang Village, Makassar City. This research uses the theory of Arif and Bintoro Tjokroamidjojo with the indicators of regulator, motivator, dynamist, facilitator and mobilizer. This type of research is descriptive with a qualitative approach. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions. The results of this research show that the Tompo Balang sub-district, Makassar City, has carried out its role as a regulator, motivator, dynamist, facilitator and mobilizer. However, the facilitator and mobilizer indicators have not been implemented optimally because the facilities provided have not been implemented evenly and there has been no follow-up to the stalled waste management program. The supporting factor for the government's role in waste management in Tompo Balang sub-district, Makassar City is that waste is the main program of the Makassar City government and sub-district areas that have waste sources. Factors inhibiting the government's role in waste management in Tompo Balang sub-district, Makassar City are the lack of waste management facilities and infrastructure as well as the low level of public awareness of waste management